Evaluating the method increasing of toric intraocular lenses rotational stability - G. A. Fedjashev (Oftalʹmologiâ)
Purpose. To suggest a safe and effective way to improve the rotational stability of the position of toric the intraocular lenses in the capsular bag.Patients and methods.86 patients (97 eyes) with corneal astigmatism undergoing cataract surgery and Acrysof Toric (Alcon, USA) intraocular lens implantation. In 42 patients (47 eyes), the intraocular lens (IOL) were implanted in accordance with the proposed invention.Results. Average rotation angle IOL implanted by traditional technology was 2,2±2,0 degrees during 12 months. In patients with IOL implanted by the proposed method, the average angle of rotation of the IOL in all operated eyes was significantly lower and amounted to 0,8±1,2 degrees (p <0,05). Сonclusion. The proposed method of fixing the toric IOL provides for prevention the IOL rotation and decentration relative to the eye optical axis, take steps to prevent phimosis anterior lens capsule, maintaining high visual function for a long time, and as there is no need for repeated surgery.